Or Orwell : writing and democratic socialism - Woloch, Alex, 1970- (Harvard University Press, 2016)
"'Good prose is like a window-pane, ' Orwell famously avers. But what kind of literary criticism is possible, face-to-face with Orwell's plain-style prose? Too often this style has been either dismissed by a seemingly more savvy critical theory, or held up as a reprimand against the enterprise of theory. In a series of unusually close and intensive readings--focused on the unstable event of writing itself--Woloch recovers the radical and experimental energies of Orwell's prose. Against accounts that would quickly naturalize Orwell's truthfulness or reduce his window-pane prose to bad faith, Woloch's study bears down on a propulsive irony and formal restlessness that have always been intertwined with Orwell's plain-style. Such restlessness, far from diluting Orwell's democratic and socialist politics, is at its aesthetic and conceptual core."--Publisher's Web site